Slow post-orogenic cooling in a deeply eroded orogen: Reindeer Zone, Trans-Hudson Orogen, Saskatchewan - Chakungal, Joyia; Reynolds, Peter H; Jamieson, Rebecca A; Corrigan, David (Canadian Journal of Earth Sciences, 2004)
We present 40 Ar/ 39 Ar hornblende and muscovite data from a 200 km transect across the northern flank of the Paleoproterozoic Trans-Hudson Orogen (THO) exposed along Reindeer Lake in Saskatchewan, Canada. The transect crosses a series of distinct lithotectonic domains that experienced pressuretemperature (PT) conditions of 600730 °C at 4.56.0 kbar (1 kbar = 100 MPa) during D 2 peak metamorphism at 18201790 Ma. The distribution of 40 Ar/ 39 Ar hornblende ages shows that most of the transect cooled through approximately 500 °C by ca. 1765 Ma, with two significant exceptions. At the north end of the transect, older ages in the Peter Lake Domain (up to 2200 Ma) suggest that this region did not experience high-grade metamorphism that affected the rest of the transect and may indicate a structural break between these Archean rocks and the Cree Lake Zone to the north. In the south-central part of the transect, UPb (monazite, titanite) and 40 Ar/ 39 Ar (hornblende, muscovite) ages indicate that rocks in the vicinity of the Duck Lake Shear Zone, a ductile thrust zone separating the Kisseynew and La Ronge domains, cooled at a rate of 6 °C/Ma and that cooling was delayed by ca. 2025 million years relative to that of adjacent regions. Based on generic thermaltectonic models for large hot orogens, we suggest that delayed cooling in the vicinity of the shear zone reflects post-orogenic thermal relaxation of lower crustal isotherms that were perturbed by the effects of convergence.